Effects of water and nitrogen coupling on growth, physiology and yield of rice - Li, Yuanyuan; Shao, Xiaohou; Li, Daoxi; Xiao, Menghua; Hu, Xiujun; He, Jing (International Journal of Agricultural and Biological Engineering, 2019)
Water and nitrogen fertilizer are two essential factors for quality and yield formation of rice. Experimental study was carried out to investigate the effects of water and nitrogen fertilizer coupling on yield-related factors, such as growth (height), physiological indicators (chlorophyll and leaf area index (LAI)) and yield composition indicators (productive panicles, thousand grain weight and total grains per panicle). Results showed that, the height difference under two irrigation regimes was not significant, and it showed no difference until the tillering stage (p > 0.05). The water control method for controlled and mid-gathering irrigation (CMI) was favorable for nutrients converting to rice grain. Meanwhile the height difference for CMI and conventional irrigation (CVI) was the biggest at 80 d after rice transplantation. Variance analysis showed the effect of fertilization on height was significant (p < 0.05). With organic fertilizer application, it could control plant growth and promote the nutrients converting to the panicle. The change curve of LAI was similar to chlorophyll content. Organic fertilizer application could not only promote chlorophyll content and LAI, but also delay leaf fading and promote yield. Nitrogen fertilizer factors showed significant difference on rice yield, compared to irrigation regimes showing no significance. Considering the irrigation and fertilizer factors together, the interaction was significant. The descending orders for the effects of water and nitrogen on rice yield were fertilizer, water and fertilizer, water. Regression analysis showed that the productive panicles and total grains per panicle of rice were extremely significant on rice yield, and the direct effect of total grains per panicle on yield was greater than that of productive panicle. This study results could provide theoretical basis for water and nitrogen management to improve rice production.Keywords: water and nitrogen coupling, controlled and mid-gathering irrigation (CMI), organic fertilizer, growth and physiology, regression and path analysis, rice yieldDOI: 10.25165/j.ijabe.20191203.4060Citation: Li Y Y, Shao X H, Li D X, Xiao M H, Hu X J, He J. Effects of water and nitrogen coupling on growth, physiology and yield of rice. Int J Agric & Biol Eng, 2019; 12(3): 60–66.